改質聚醯胺之雙分子界面活性劑製備、界面性質分析及以田口法分析其 染整加工條件最佳化研究 - 賴秋君 (2019)
本研究計畫目的在於將Jeffamine進行改質，合成雙分子界面活性劑，形成生質高分子之界面活性劑，探討一系列生質高分子Jeffamine改質界面活性劑界面性質，包含表面張力、臨界微胞濃度、濕潤性、乳化性，建立界面科學基礎數據，並應用於染色加工，經由田口方法探討其染色加工最佳化參數。由於綠色環保趨勢，藉添加此綠色界面活性劑於染色製程中，期望能降低染色廢水的污染。藉此應用於紡織染整產業，並由於綠色環保趨勢，藉添加此綠色界面活性劑於染色製程中，期望能降低染色廢水的毒性污染，提升染整產業綠色化學品技術能量，增進產業應用性，並進而提高附加價值。 The purpose of this project is mainly to synthesize the modified gemini polyamide interfacial active agent to improve the inconvenience of the traditional surfactants. The modified gemini surfactant is composed of Jeffamine and long Carbonic acid and a single acid or diacid as raw materials to synthesize a series of modified nonionic and anionic non-ionic bimolecular surfactants. In addition to investigating the interfacial properties of three different types of surfactants (single-molecule surfactants, non-ionic bimolecular surfactants and anionic non-ionic bimolecular surfactants),the surface-activities including surface tension, cmc, wetting, emulision, pH buffer capacities, dispersibilities, scouring and other properties are measured to build database, and than application in dyeing process.